2021
DOI: 10.1111/jfpe.13690
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on appropriate two‐stage drying techniques for quality paddy seeds

Abstract: An attempt was made to investigate appropriate two-stage drying techniques for quality of paddy seeds. In this research, two options of two-stage drying were conducted for three varieties of paddy and Guti Swarna). In both options, first stage drying was carried out by a fluidized bed dryer using three temperatures (50, 55, and 60 C) at constant bed thickness of 15 cm. After tempered, in the first option, samples were further dried in second stage by sun drying (28-32 C).In the second option, samples were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The highest germination capacity (88%) of hybrid rice seed in thin layer drying at 40°C drying temperature (Hasan et al, 2014). The maximum germination percentage of rice seeds was found at the first stage 50°C and the second stage 35°Cdrying air temperature dried in a fluidized bed dryer (Islam et al, 2021). In this research, the highest germination percentage was found for wheat seeds at 40°C dried in a fluidized bed dryer.…”
Section: Comparison Of Germination Percentage Between Fluidized Bed D...mentioning
confidence: 50%
See 1 more Smart Citation
“…The highest germination capacity (88%) of hybrid rice seed in thin layer drying at 40°C drying temperature (Hasan et al, 2014). The maximum germination percentage of rice seeds was found at the first stage 50°C and the second stage 35°Cdrying air temperature dried in a fluidized bed dryer (Islam et al, 2021). In this research, the highest germination percentage was found for wheat seeds at 40°C dried in a fluidized bed dryer.…”
Section: Comparison Of Germination Percentage Between Fluidized Bed D...mentioning
confidence: 50%
“…Sun-drying is a natural source of drying and one of the most primitive and common methods of drying wheat seed (Islam et al, 2021). Laborintensive traditional sun-drying methods for wheat seed drying may not be economic and safe soon where the infestation is common.…”
Section: Introductionmentioning
confidence: 99%
“…The average initial moisture content for the seeds was then obtained to be 69.4 ± 1% (d.b.) using Equation (1) (Islam et al, 2021) . MC%d.b.=WwWdWd×100 where MC is the initial moisture content of the seeds based on dry weight (%), Ww is the sample weight before oven drying (g), and Wd denotes the dried sample weight (g). A summary of some physical properties of dried cumin seeds was shown in Table 1.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The average initial moisture content for the seeds was then obtained to be 69.4 ± 1% (d.b.) using Equation (1) (Islam et al, 2021) .…”
Section: Sample Preparationmentioning
confidence: 99%
“…These dishes were then subjected to a drying process in an oven for the duration of 24 h at a temperature of 105 C (Babaki et al, 2020). Using Equation (1), the average on initial moisture content of bitter melon was found to be 12.33 ± .5 g of water per gram of dry matter (Islam et al, 2021).…”
Section: Preparation Of Samplesmentioning
confidence: 99%